1965
DOI: 10.1590/s0071-12761965000100020
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos ecológicos e bionômicos das saúvas da região oriental do Estado de São Paulo

Abstract: Neste trabalho, são descritos aspectos ecológicos, distribuição por município, importância econômica, etc., das saúvas encontradas na Região Oriental do Estado de São Paulo. Esta região, cuja conformação se assemelha a um "bico", está dividida em 52 municípios. Três espécies de saúva foram encontradas: l.ª) "saúva limão" ou "saúva comum" Atta sexdens rubropilosa Forel, 1908; 2.ª) "saúva mata pasto" A. bisphaerica Forel, 1908; 3.ª) "saúva de vidro" ou "saúva cabeça de vidro" A. laevigata (F. Smith, 1858).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

1966
1966
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…The absence of other Atta species in restinga vegetation in Rio de Janeiro and Espírito Santo states is also noteworthy. According to Mariconi (1965) Gonçalves & Nunes (1984) Fowler (1995) e Fowler et al (1996) Restinga localities sampled in the present work…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The absence of other Atta species in restinga vegetation in Rio de Janeiro and Espírito Santo states is also noteworthy. According to Mariconi (1965) Gonçalves & Nunes (1984) Fowler (1995) e Fowler et al (1996) Restinga localities sampled in the present work…”
mentioning
confidence: 66%
“…The hypothesis that A. robusta is restricted to the Moist Oriental Tertiary Brazilian Coast is reinforced by results obtained by other authors who studied ant fauna in regions located in the South of Serra do Mar and North of Espírito Santo. Mariconi (1965) studied the Oriental region of São Paulo State, where littoral and restinga vegetation are included, not revealing the presence of A. robusta. Bonnet & Lopes (1993) carried out an ant survey in dune and restinga vegetation further Southern in Santa Catarina state, and neither have found A. robusta.…”
mentioning
confidence: 99%
“…These authors also suggested that A. robusta does not disperse southward because of the Serra do Mar mountain range present in the southern part of Rio de Janeiro state. Indeed, this species has not been found in restingas of the states of São Paulo (Mariconi, 1965), Santa Catarina (Bonnet and Lopes, 1993) and Paraná (Lopes, 1998). The superficial water table in São Paulo state could also contribute to the absence of A. robusta along the coast of this state since this water may interfere in nest development (Mariconi, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this species has not been found in restingas of the states of São Paulo (Mariconi, 1965), Santa Catarina (Bonnet and Lopes, 1993) and Paraná (Lopes, 1998). The superficial water table in São Paulo state could also contribute to the absence of A. robusta along the coast of this state since this water may interfere in nest development (Mariconi, 1965). Teixeira et al (2003) emphasized that there is no record of A. robusta in the state of Bahia, despite the lack of any evident geographical barrier to impede the northward dispersion of this species beyond Espírito Santo.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com MARICONI (1970) as operárias se divi dem em castas caracterizadas principalmente pelo tamanho dos indi víduos, divisão um tanto arbitrária, pois. num mesmo grupo cabem formigas de tamanhos um tanto diferentes e ainda, segundo HOWSE e BRAOSHAN (1977) essa tal divisão não pode ser feita nem em termos de comportamento.…”
Section: Revisão De Literaturaunclassified